1963
DOI: 10.1021/jm00338a010
|View full text |Cite
|
Sign up to set email alerts
|

New Psychotropic Agents.1a IV. Derivatives of Dibenzo[a,d][1,4]cycloöctadiene

Abstract: The residue was treated with 50 nil. of * hydrochloric acid and the aqueous solution was extracted with ether. The ether layer was discarded. The aqueous layer was made alkaline by the addition of 15 ml. of 5 X sodium hydroxide and the organic base was extracted into ether. The ether layer was washed with water, dried over magnesium sulfate and distilled. A low-boiling forerun -was discarded and (-)V was collected at 144-148°(0.08 mm.). The yield was 4.6 g. (57%), zz25d 1.562, [a]25u -18.8°.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1963
1963
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…6-(Iodomethyl)-5,6.11>12-tetrahydrodibenzo[o,e]cycloocten-5-one (10). Yield of crude product (oil): 99%.…”
Section: Methodsmentioning
confidence: 99%
“…6-(Iodomethyl)-5,6.11>12-tetrahydrodibenzo[o,e]cycloocten-5-one (10). Yield of crude product (oil): 99%.…”
Section: Methodsmentioning
confidence: 99%
“…Found: C, 81.20; H, 6.42. 10-Cyano-5.ff-dibenzo[a,d]cyclohepten-5-one (6). A. Bromination.-A solution of 12.7 g of keto nitrile 5a and 12 g of bromine in 300 ml of benzene was let stand 2 days (room temperature). The ether-diluted, washed (NaHCOs solution, water) and dried solution on evaporation gave 18 g of crude bromo keto nitrile, a slightly fuming, viscous, yellow oil which did not crystallize.…”
Section: Experimental Section43mentioning
confidence: 99%
“…Similar hydrogenolysis of keto acid 8a gave acid 12. Amide 11a was also obtained from acid 12 as shown.…”
mentioning
confidence: 99%
“…Thus it was necessary to have available a series of mono-and di-6-substituted 5,6,7,12-tetrahydrodibenzo [a, d]cyclooctenes 1 and this paper describes the synthesis of these compounds. The only other carbocyclic compounds reported in the literature having the skeleton of 1 are those with substitution at C-12 (3). These were prepared according to Scheme 1 where R, = R2 = EI.…”
mentioning
confidence: 99%
“…Also, Winthrop et ul. (3) found that the cyclization step was very sensitive to structural change in the reactants, and in some cases the desired cyclization product was not obtained. ' The reaction sequence chosen by us is shown in Scheme 2.…”
mentioning
confidence: 99%